Two Live Births following Robotic-Assisted Abdominal Cerclage in Nonpregnant Women - Ahmet Göçmen; Fatih Şanlıkan (Case Reports in Obstetrics and Gynecology)
Introduction. To report the robotic-assisted abdominal cerclage performed in two nonpregnant women and the success of live birth outcomes. Presentation of Cases. A 36-year-old woman with a complaint of recurrent second trimester pregnancy losses and a 35-year-old patient with a complaint of preterm deliveries and cervical insufficiency underwent robotic assisted abdominal cervicoisthmic cerclage placement in nonpregnant period. The two patients had spontaneous pregnancy after the robotic-assisted abdominal cerclage and delivered healthy infants. Discussion. The limitations of traditional laparoscopic abdominal cerclage have been accomplished with robotic surgery advantages especially intuitive movements and increased range of motion. There are only a few studies in the literature including robotic assisted abdominal cerclage in nonpregnant women, and only five successful live birth outcomes were reported. In this paper, we reported the sixth and seventh cases of achieved live pregnancy after robotic assisted abdominal cerclage in the literature. Conclusion. Robotic assisted abdominal cerclage is a good alternative surgical method with successful pregnancy outcomes.